2001
DOI: 10.1002/j.2161-1920.2001.tb00496.x
|View full text |Cite
|
Sign up to set email alerts
|

Job search methods, job search outcomes, and job satisfaction of college graduates: a comparison of race and sex

Abstract: A nationally representative sample of college graduates (N =11,152) were surveyed regarding their job‐seeking behaviors and outcomes. Race and sex differences among the job search strategies used, number of job interviews, number of job offers, annual salary, and job satisfaction were examined. Results indicated significant race and sex differences in job search methods used. There were significant differences in underemployment and job satisfaction as a function of race, and in underemployment and annual sala… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
49
1
4

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(57 citation statements)
references
References 35 publications
3
49
1
4
Order By: Relevance
“…through friends; to select their jobs compared to males. These results differ from those of Mau and Kopischke (2001). They reported that female and male graduates did not differ in their use of the network system to obtain their jobs and that males were more apt to make a formal application to obtain a job.…”
Section: Discussioncontrasting
confidence: 81%
See 2 more Smart Citations
“…through friends; to select their jobs compared to males. These results differ from those of Mau and Kopischke (2001). They reported that female and male graduates did not differ in their use of the network system to obtain their jobs and that males were more apt to make a formal application to obtain a job.…”
Section: Discussioncontrasting
confidence: 81%
“…To do this, the effects of job procurement on satisfaction and occupational performance were examined using structural or social variables. This study is in the tradition of those by Steffy, Shaw, and Noe (1989); Stumpf, Austin, and Hartman (1984); and Mau and Kopischke (2001). Specifically, the following dimensions were scrutinized: (a) graduate job selection and procurement methods; (b) differences in job-procurement methods between graduates from public and private universities; (c) job procurement and its relation to graduates' occupational attainment, i.e.…”
Section: Purpose Of the Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, a larger proportion (ten percentage points) of the former is found in the higher income group. However, these findings were only replicated by a few studies (Corcoran et al, 1980;Staiger, 1990;Wegener 1991;Coverdill, 1994;Jann, 2003), while many others could not detect a wage differential (Lin et al, 1981;Bridges and Villemez, 1986;Marsden and Hurlbert, 1988;Preisendörfer and Voss, 1988;Lin, 1999;Mau and Kopischke, 2001). Some studies (De Graaf and Flap, 1988;Flap and Boxmann, 2001) even find a negative wage effect for social contacts.…”
Section: Introductionmentioning
confidence: 81%
“…11, No. 17;2015 study done by Mau & Kopischke (2001) reported that gender influenced job-search intensity, and also career decision-making (Melati, 2006;Gushue, 2006;Foster, 2005).…”
Section: Discussionmentioning
confidence: 99%